GUIDELINE FOR CREATIVE TOURISM MANAGEMENT BASE ON SOCIAL CAPITAL AND CULTURAL CAPITAL IN KOH KRET COMMUNITY, NONTHABURI PROVINCE - Phuensa-ard, Banjarong (Journal of MCU Nakhondhat, 2023)
The objectives of this research article are 1) to study the social capital and cultural capital of Koh Kret community, Nonthaburi province and 2) to propose a guideline for creative tourism management based on social capital and cultural capital of Koh Kret community, Nonthaburi province with the use of qualitative research. The sample group was people involved in tourism management of Koh Kret and Key informant about social capital and cultural capital, total 30 people, whereas interview form and focus group were used. 1) The results of the research social capital and cultural capital of Koh Kret consist is a network of various groups in Koh Kret community that work together to coordinate tourism in the community and community development. The cultural capitals of Koh Kret are Mon culture; the traditional occupation is making Mon pottery. In terms of food, Khao Chae Mon cooking has been inherited as well as Khao Chae parade, Sweet Drinks parade and Hang Hong parade which are highlights in term of tradition; Thai Buddhist culture; the Buddhists have career in fruit orchards agriculture. As for the food aspect, there are fried coconut shoots and traditional Thai desserts. The tradition aspect is the tradition of offering alms to flowers as the highlight and Thai Muslim culture; the highlight activities are batik cloth making, Muslim food and desserts cooking such as Salaman, Curry Noodles, Chicken Biryani, Khanom Badin and Jamu Jamu dessert. 2) The results of the presentation of a creative tourism management guideline for Koh Kret, the research found that there are 5 patterns of creative tourism activities, namely 2.1) Mon pottery route pattern; 2.2) Traditional Thai dessert learning activity pattern; 2.3) Health promotion route pattern; 2.4) Batik cloth and Muslim food and desserts learning activity pattern and 2.5) Rivers of three cultures learning activity pattern.